The composition of the electrode deposit in the Moore lamp - Haslam, T. P. (My University, 1908)
Introduction: The Moore lamp consists essentially of a piece of glass tubing one and three-fourths inch in diameter and four or more feet in length, into both ends of which are sealed carbon electrodes. The tube contains a gas under a pressure of about .1 mm of mercury.
Citation: Haslam, T. P. The composition of the electrode deposit in the Moore lamp. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Lamps; Electricity; Engineering; Graduating theses; Senior theses; Theses